Christian Names of Karelians - Denis V. Kuzmin (Вопросы Ономастики, 2016)
The article analyses the forms of Christian names used in the past and in the present on the territory of the Karelian ethnic group’s settlement — in Finland, as well as in Russian Karelia, Tver and Leningrad regions. The main aim of the article is to sum up the findings of previous research and to provide an analysis of new anthroponymic data retrieved from the 16th–17th centuries historical documents or collected by the author and other researchers during field trips. After outlining the main stages of the development of the Orthodox religion on the Karelian lands, the author gives an insight into the history of the formation of the Karelian Orthodox anthroponymicon. The article shows that after the adoption of Orthodox religion in 1227 Karelians adopted a large number of Christian names which later were modified according to the phonetic and morphologic patterns of the Karelian language. In Karelian, canonical Christian names received numerous folk variants, part of which derived from the Russian language forms used on the neighboring Russian lands. The article focuses on the main ways of phonetic and morphological adaptation of Russian forms in the Karelian language. The author emphasizes that Karelian forms of Christian names feature a rather well-built phonetic and morphological system, which allows not only to explain the origin of obscure forms but to restore a number of forms which might have been used earlier in the Karelian language but were completely lost.